Response of Sunflower (Helianthus annuus L.) to Different Planting Dates under Suliamani Region Condition - Aziz, Hussein Muhammed; Salih, Sarkawt Hama (Sulaimani Journal for Pure and Applied Sciences, 2014)
A field experiment was conducted during the spring season 2011 at two locations, the first location was kanipanka, in a research center, which belongs to the Ministry of Agriculture and located about 36Km south-east of Sulaimani city, and the second was conducted at the Qlyasan research center belong to the faculty of Agricultural sciences / university of sulaimani. the aim of the study was to show the effect of different plant date on growth characteristics. Yield, and yield components of Sunflower (Flamme variety). The seeds were planted on 3rd March, 18th March, and 2nd April at Kanipanka, while the dates were 14th March,19th March, and 3rd April at Qlyasan location, the completely Randomized Design (CRBD) was done within three replications in both locations. The results must be shown the existence of significant differences of the effect location of most traits growth characteristics , yield and its components, where the superiority location (kanipanka) in each of the characteristic of stem length, disk diameter, number of seeds / plant, seed weight / plant, seed weight, dry matter yields, seed yields, oil yields and bio- yields location (Qlyasan). However were not significantly affected by different planting date on traits root depth, number of disks / plant and number of leaves / plant.
Keywords: Sunflower; Planting date; Growth characters; Yield component